Archiving Knowledge Transmission in Islamic Educational Institution: The Case of Pesantren Miftahul Huda Tasikmalaya, Indonesia - Rully Khairul Anwar; M. Taufiq Rahman (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2019)
This paper discusses the archiving system of knowledge transmission in traditional Islamic educational institution in Indonesia. The process of knowledge transmission in Islamic traditional educational institution cannot be separated from its position as the center of Islamic education and information. This study focuses its analysis on the Pesantren Miftahul Huda, Tasikmalaya, Indonesia, using qualitative method and data collection techniques through observation and interview. The results show that archiving knowledge transmission was limited and not well-managed in the pesantren Miftahul Huda. The pesantren was traditional in its archiving system in that it relied on the teachers’ memories in the process of transmission of Islamic science. To maintain an archiving system in traditional Islamic educational institution, pesantrens in Indonesia must pay serious attention to the archiving of their documents and activities for practical and scientific purposes. The support of local and central government support and other parties will be valuable and useful for these purposes.